Synthesis and characterization of siloxane copolyesters containing phenylindane linkages - Waghmare, P. B.; Deshmukh, S. A.; Idage, Susheela B.; Idage, Bhaskar B. (Journal of Applied Polymer Science, 2006)
A novel series of siloxane copolyesters containing 1,1,3-trimethyl-3-(p-hydroxyphenyl)-5-indanol (phenylindane bisphenol), diphenyl terephthalate (DPT), diphenyl isophthalate (DPI), and eugenol end-capped siloxanes in varying ratios were prepared at a temperature range of 200-290 degrees C under reduced pressure using dibutyl tin dilaurate catalyst by melt polycondensation. The siloxane-containing copolyesters were characterized by infrared and H-1 NMR spectroscopy, elemental analysis, solution viscosity, thermogravimetric analysis, differential scanning calorimetry, and X-ray diffraction. The effect of incorporation of siloxane moiety was studied on the properties of phenyl indane/DPT/DPI coplyester. The glass transition temperatures of copolyesters were decreased from 235 to 124 degrees C by incorporation of 10% eugenol end-capped siloxane without affecting the thermal properties. All copolyesters were found to be soluble in commonly used organic solvents and had film forming properties. (c) 2006 Wiley Periodicals, Inc.
Keywords: eugenol end capped siloxane; melt polymerization; phenylindane bisphenol; siloxane copolyesters